EXPERIMENTAL INVESTIGATION OF SOLAR STILLS INTEGRATED WITH SOLAR WATER HEATING COLLECTORS - Emin, E. L.; Cakmak, Gulsah; Argunhan, Zeki; Yildiz, Cengiz (Turkish Soc Thermal Sciences Technology, 2017)
Solar still is a more practical way of obtaining clean water. In this study, we aimed to improve the efficiency of solar still systems and obtain distilled water at the same time. For this purpose, 5 different solar still systems were designed. Type 1; conventional solar still, Type 2; conventional solar still integrated with solar water heating collector and run via natural convection, Type 3; conventional solar still integrated with solar water heating collector and tubular heat exchanger and run via natural convection, Type 4; conventional solar still placed with plate heat exchanger and integrated with solar water heating collector and run via natural convection, Type 5; conventional solar still placed with plate heat exchanger and integrated with solar water heating collector and run via forced convection. In this study, the experiments were carried out on the parameters influencing the performance, the amount of distilled water obtained, and the efficiency of experiment settings designed in different types; and finally the results were presented. The amount of distilled water and efficiency of conventional solar still were 2389 ml and 51.47%, respectively. Maximum total amount of water and efficiency from natural convection systems were obtained from Type 4, and the values calculated were found as to be 5788 ml and 55.91%. Maximum amount of distilled water and the efficiency were obtained by utilizing forced convection system were found as to be 6068 ml and 58.99%, respectively.
Keywords: Solar water heater; Solar water distillation; Efficiency